2023
DOI: 10.2196/46761
|View full text |Cite
|
Sign up to set email alerts
|

Chatbots to Improve Sexual and Reproductive Health: Realist Synthesis

Abstract: Background Digital technologies may improve sexual and reproductive health (SRH) across diverse settings. Chatbots are computer programs designed to simulate human conversation, and there is a growing interest in the potential for chatbots to provide responsive and accurate information, counseling, linkages to products and services, or a companion on an SRH journey. Objective This review aimed to identify assumptions about the value of chatbots for SRH … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…This study concluded that chatbots can be of significant value in improving the reproductive health of patients in need. 31 Another study by Okeibunor and colleagues demonstrated that currently, ML and DL algorithms have primarily been utilized with the aim of detection, diagnosis, management, and monitoring for the delivery of different healthcare services, including reproductive health. 32 In Pakistan, many adolescents are at risk of poor reproductive health, which is associated with poor parenting, early childbearing, and pregnancy-related complications.…”
Section: Target 33 Infectious Diseasesmentioning
confidence: 99%
“…This study concluded that chatbots can be of significant value in improving the reproductive health of patients in need. 31 Another study by Okeibunor and colleagues demonstrated that currently, ML and DL algorithms have primarily been utilized with the aim of detection, diagnosis, management, and monitoring for the delivery of different healthcare services, including reproductive health. 32 In Pakistan, many adolescents are at risk of poor reproductive health, which is associated with poor parenting, early childbearing, and pregnancy-related complications.…”
Section: Target 33 Infectious Diseasesmentioning
confidence: 99%
“…Teenagers may easily use and scale up AI-powered chatbots to get information, advice, and support on sexual and reproductive health. These virtual assistants provide a private, judgment-free forum for debates by involving users in real-time dialogues [38,39].…”
Section: Challenges and Opportunities For Mhealth Interventionsmentioning
confidence: 99%
“…Chatbots may use rule-based language applications or more advanced natural language processing (NLP) and artificial intelligence technology to automate conversations [ 7 ]. In the context of contraception, chatbots have the potential to provide rapid and responsive information, counseling, and linkages to products and services [ 8 ]. They may also serve as navigational agents and companions on a reproductive health journey or be gamified and serve as “edutainment” [ 9 ].…”
Section: Introductionmentioning
confidence: 99%